SOCIAL AND POLITICAL DISCOURSE IN THE CONTEXT OF TEACHING ENGLISH - Ruslan M. Kliuchnyk (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
The article considers some aspects of the use of social and political discourse in teaching English. In the article, social and political discourse means all the messages that are related to social and political issues. The new trends of modern media development are considered. Some aspects of use of mass media in education have been considered. In particular, special attention has been paid to the main peculiarities of mass media as a source of educational content. The didactic potential of newspapers, radio, television and the Internet have been shown. It has been demonstrated that the use of politically charged lexicon (not only politically correct words and expressions but also pejorative once) broadens students` outlook and trains them to work in different social and political conditions. For example, euphemisms should be used in the modern political communication in order to avoid conflicts. It has been proved that newspaper texts can help us study history of the countries of the languages being learnt. The difference between the quality press and tabloids has been explained. A table of headlines is given to illustrate historical events in the USA and the world. The activity of English mass media in facilitating English learning has been considered. It has been demonstrated that some materials issued by the BBC are aimed at familiarizing the audience with the English language. E.g., the English Express project contains video materials and some brief data about the English grammar as well as tests. The author has emphasized that media often contain wrong, biased or fake information. Fake news is considered as a threat to the stability of communication. It is shown that the students should try to verify all the messages they use in their activities. All types of communication on the Internet and wherever else should meet both legislation and ethical principles. Special attention is paid to blogs as alternative sources of information. The authors of blogs express different opinions and they do not have to follow any editorial lines. It has been shown that working with webpages increases the level of media literacy of the students. Special attention is paid to the sources created intentionally for language exchange, e.g. Interpals and Duolingo. It is underlined that the students should not only perceive but also create media content. The use of Facebook, Youtube, Wikipedia, Livejournal etc. can facilitate the publication of the students` achievements. The author has paid attention to activities that can be done using media materials, e.g. project work, simulations and others.